Contrasts in Mirouer des femmes vertueuses - Materka, Paulina (Contrasts in humanities: literature, language, culture, 2023)
Our article is focused on the contrasts in the Mirouer des femmes vertueuses, an anonymous collection of two stories: one about Joan of Arc and the other about Griselidis. We compare opposing aspects of these characters. Firstly, we counterpose the discursive character of the heroines, where one is real and the other is fictional. Then we study different qualities, the two models of femininity and finally the behaviour of the character in question in the face of events.